The Urgency of Amendment to Law Number 32 of 2002 concerning Broadcasting as the Legal Umbrella for OTT Services - Neysa Tania; Rio Kurniawan (Constitutionale, 2020)
Digitalization is a global phenomenon that has an impact on changing social conditions. The Broadcasting Bill itself is canceled to be a priority in the 2020 Priority National Legislation Program even though there is a lot of material contained in the law itself needs to be updated immediately according to the times. Therefore, the function of conducting this research is to seek answers in terms of legal certainty regarding the development of legal relations with technological developments in the era of digitalization and constitutional interpretation in the digitalization era that supports sustainable economic development and is in accordance with the Indonesian national identity. This study uses a quantitative juridical analysis method, which is in the form of in-depth research on legal materials and data as usual as normative law. Furthermore, the results of the analysis will be linked to the problems in this study to produce an objective assessment to answer the problems in the research. The results of the research show that the OTT services cannot be in the scope of Law Number 32 of 2002 concerning Broadcasting, therefore the Constitutional Court must play a strategic role in carrying out rapid and precise reforms so that statutory norms can be consistent with the development of society, especially due to developments. Digital technology. The most ideal and relevant constitutional interpretation of the Judicial Review case against this law would be: Consensualism, Prudential and Futuristic with an emphasis on legal certainty for Over the Top (OTT) services and on socio-economic impacts significant impact on the general welfare. It is necessary to revise the Broadcasting Law with the intention of maintaining national integration to establish a national broadcasting system that guarantees the creation of a just, equitable, and balanced national information order in order to realize social justice for all Indonesian people.